The Existence of Javanese Language in Wonomulyo: A Philosophical and Multicultural Study - Mulyana Ramadhani, Dita; Prayetno, Budi; Ikhsan, Taufik; Tri Nova, Sigit; Nazaruddin, Nazaruddin (Information Technology and Science(ITScience), 2025)
This study examines the existence of the Javanese language in Wonomulyo within a multicultural context, identifies factors supporting and inhibiting its maintenance, and interprets its significance through the philosophy of language. Using a qualitative case study approach, data were collected through interviews, participant observation, and documentation involving community leaders, teachers, parents, and youths. The findings indicate that Javanese continues to maintain moderate vitality, particularly within family, community, and cultural–ritual domains such as selamatan and kenduren. In these contexts, Javanese functions not only as a means of communication but also as a medium for transmitting moral values, social etiquette, and collective identity, especially through the practice of unggah-ungguh. However, language maintenance faces significant challenges. The dominance of Indonesian in formal education, public spaces, and digital communication has led to a gradual narrowing of Javanese use, particularly among younger generations. While youths remain bilingual, Indonesian is increasingly associated with modernity and mobility, whereas Javanese is largely confined to symbolic and intimate domains. From a philosophical perspective drawing on Wittgenstein, Heidegger, and Foucault, the study argues that the weakening of Javanese reflects not only linguistic change but also shifts in meaning, identity, and power relations. The study highlights the need for integrated efforts involving families, communities, education, and digital spaces to sustain regional languages in multicultural societies.